Effect of Plant Density on the Performance of Two Sesame (Sesamum indicum L.) Cultivars under Irrigation * (University of Khartoum Journal of Agricultural Sciences, 2025)
A field experiment was conducted for two consecutive seasons(2000/01 and 2001/02) at Kenana Sugarcane Research Farm to investigatethe effect of planting density on the performance of two cultivars ofsesame (Sesamum indicum L.); namely, Khidir and Promo. The plantswere sown at four planting densities: 5, 10, 15 and 20plants/m 2 (0.5x10 5 ,1.0x10 5 ,1.5x10 5 and 2.0x105 plants/ha, respectively).The treatments were arranged in a randomized complete block designwith four replications. The results indicated that the leaf area index anddry matter production increased with increasing plant density. Increasingplant density significantly decreased the number of capsules per plant,number of seeds per capsule and seed yield per plant, and increased seedyield per unit area. There were no significant differences in oil andprotein content between plant densities. The differences between the twocultivars were significant in all the studied characters, and Promo cultivaroutyielded Khidir by 11% in the first season and by 22 % in the secondseason. The higher yield of Promo was associated with higher number ofcapsules per plant and greater number of seeds per capsule.It is recommended that irrigated sesame should be sown at a stand densityof approximately 15-20 plants/m 2 (1.5x10 5 –2.0x10 5 plants ha-1 ).